PENGARUH MODEL PROJECT BASED LEARNING (PjBL) DENGAN PENDEKATAN STEM TERHADAP HASIL BELAJAR MAHASISWA - Din Mahdiansyah; Aceng Haetami; Fahyuddin Fahyuddin; Saefuddin Saefuddin; Muhamad Alim Marhadi; Maysara Maysara; Nada Shofa (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
This research is motivated by the low learning outcomes of basic chemistry and the diversification of academic backgrounds of first-year students that hinder in-depth understanding of concepts. The problem focuses on testing the effect of the Project Based Learning (PjBL) model integrated with the Science, Technology, Engineering, and Mathematics (STEM) approach on student academic achievement. This quantitative study applies a quasi-experimental method using a pretest-posttest control group design in two study groups. The instrument used is an objective learning outcome test consisting of 20 validated multiple-choice questions. The results show that the average posttest score of the experimental class reached 77, while the control class only obtained a score of 61. This superiority is reinforced by the achievement of the N-gain index of the experimental group of 0.6 which exceeds the control class with an achievement of 0.4. Based on the inferential independent sample t-test using the SPSS program, a significance value of 0.000 was found to be less than 0.05, indicating a significant difference in achievement. The main conclusion of the study confirms that the application of the PjBL model with the STEM approach has proven to be much more effective in boosting student learning outcomes evenly compared to the conventional model. This interdisciplinary approach successfully facilitates students in constructing a meaningful understanding of stoichiometry through applied projects that connect mathematical calculations with real scientific phenomena in the laboratory. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar kimia dasar serta diversifikasi latar belakang akademik mahasiswa angkatan awal yang menghambat pemahaman konsep secara mendalam. Masalah difokuskan pada pengujian pengaruh model Project Based Learning (PjBL) terintegrasi pendekatan Science, Technology, Engineering, and Mathematics (STEM) terhadap capaian akademis mahasiswa. Studi kuantitatif ini menerapkan metode eksperimen semu menggunakan desain pretest-posttest control group pada dua kelompok belajar. Instrumen yang digunakan berupa tes hasil belajar objektif sebanyak 20 butir soal pilihan ganda yang telah tervalidasi. Hasil penelitian menunjukkan nilai rata-rata posttest kelas eksperimen mencapai 77, sedangkan kelas kontrol hanya memperoleh skor 61. Keunggulan ini diperkuat oleh capaian indeks N-gain kelompok eksperimen sebesar 0,6 yang melampaui kelas kontrol dengan raihan 0,4. Berdasarkan uji inferensial independent sample t-test menggunakan bantuan program SPSS, ditemukan nilai signifikansi 0,000 kurang dari 0,05 yang menunjukkan adanya perbedaan capaian secara nyata. Simpulan utama penelitian menegaskan bahwa penerapan model PjBL dengan pendekatan STEM terbukti jauh lebih efektif dalam mendongkrak hasil belajar mahasiswa secara merata dibandingkan model konvensional. Pendekatan interdisipliner ini sukses memfasilitasi mahasiswa dalam mengonstruksi pemahaman stoikiometri secara bermakna lewat proyek aplikatif yang menghubungkan perhitungan matematis dengan fenomena sains riil di laboratorium.